Political Social Work Using Power to Create Social Change - Lane, Shannon R. (Springer International Publishing, 2018)
This social work book is the first of its kind, describing practical steps that social workers can take to shape and influence both policy and politics. It prepares social workers and social work students to impact political action and subsequent policy, with a detailed real-world framework for turning ideas into concrete goals and strategies for effecting change. Tracing the roots of social work in response to systemic social inequality, it clearly relates the tenets of social work to the challenges and opportunities of modern social change. The book identifies the core domains of political social work, including engaging individuals and communities in voting, influencing policy agendas, and seeking and holding elected office. Chapters elaborate on the necessary skills for political social work, featuring discussion, examples, and critical thinking exercises in such vital areas as: Power, empowerment, and conflict: engaging effectively with power in political settings. Getting on the agenda: assessing the political context and developing political strategy. Planning the political intervention: advocacy and electoral campaigns. Empowering voters Persuasive political communication. Budgeting and allocating resources. Evaluating political social work efforts. Making ethical decisions in political social work. Political Social Work is a potent reference for social work professionals, practitioners, and students seeking core political knowledge and skills to practically advance their work. For specialists and generalists alike, it solidifies political action as vital for the evolution of the field.